Waste Minimation in Production Process Electrical Panel Box at PT. X with Value Stream Mapping (VSM) Approach - Zainal Muttaqin, Aan; Kiswoyo, Danu (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
PT. X is a medium-sized company that produces electrical panel boxes. Make To Order (MTO) is considered a production process. The production process includes plate cutting, bending, welding, grinding, powder coating and assembly part by part processes. Lean Manufacturing is a philosophy started in Japanese manufacturing, to eliminate all waste from its processes while pursuing quality improvements in producing finished products. Value Stream Mapping is an important step in the lean transformation process before entering the waste elimination stage. The bottleneck that occurs can result in a lack of productivity from the company. The impact of the bottleneck is that the box panel product is not directly carried out by workers on the same day, so the box is at risk of piling up. The time required for the production process of APPL Box is 3047 minutes if converted in days is 2.1 days. This procurement process experienced a delay of 1 day from the target set by the company. There are 2 types of waste identified, namely waiting time and lack of powder coating machines.